Ionic liquid mediated synthesis of gold nanoparticles using extracts of oil palm leaves and kernel - IRFAN, MUHAMMAD (2018)
Gold nanoparticles (AuNPs) are appealing the researchers due to their promising applications in multidisciplinary fields including catalysis, optics, drug delivery, sensing and imaging and antimicrobial properties.